2004
DOI: 10.1158/0008-5472.can-04-2045
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Estrogen Receptor Signaling Triggers Epigenetic Silencing of Downstream Targets in Breast Cancer

Abstract: Alterations in histones, chromatin-related proteins, and DNA methylation contribute to transcriptional silencing in cancer, but the sequence of these molecular events is not well understood. Here we demonstrate that on disruption of estrogen receptor (ER) ␣ signaling by small interfering RNA, polycomb repressors and histone deacetylases are recruited to initiate stable repression of the progesterone receptor (PR) gene, a known ER␣ target, in breast cancer cells. The event is accompanied by acquired DNA methyla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
140
1

Year Published

2005
2005
2008
2008

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(147 citation statements)
references
References 43 publications
6
140
1
Order By: Relevance
“…Collectively then, the summarised findings suggest that impairment of the HNF1b/ HNF4a signalling network may lead to tumour formation. Similar epigenetic inactivation of a critical regulator of a transcriptional network has been reported for several other genes, including estrogen receptor (Leu et al, 2004) and GATA (Akiyama et al, 2003). Epigenetic inactivation of such transcription factors may affect multiple downstream genes, causing aberrant alteration of signalling pathways involved in a wide array of cellular functions, including growth, differentiation and apoptosis.…”
Section: Discussionsupporting
confidence: 53%
“…Collectively then, the summarised findings suggest that impairment of the HNF1b/ HNF4a signalling network may lead to tumour formation. Similar epigenetic inactivation of a critical regulator of a transcriptional network has been reported for several other genes, including estrogen receptor (Leu et al, 2004) and GATA (Akiyama et al, 2003). Epigenetic inactivation of such transcription factors may affect multiple downstream genes, causing aberrant alteration of signalling pathways involved in a wide array of cellular functions, including growth, differentiation and apoptosis.…”
Section: Discussionsupporting
confidence: 53%
“…Silent ERa target gene promoters have also been shown to accumulate DNA methylation following induced depletion of ERa (Leu et al, 2004). Nevertheless the opposite is not true.…”
Section: Discussionmentioning
confidence: 99%
“…53,54 Volpe et al have reported that heterochromatic silencing and histone H3 K9 methylation are regulated by RNAi, 55 and it has been suggested that small interfering RNAs (siRNAs) regulate DNA methylation of promoter regions. 55,56 Hence, it is apparent that DNA methylation, histone modification and RNAi are intimately related to each other, 54,57 and comprehensive epigenetic studies in which these 3 mechanisms are examined will be necessary to confirm the details of regulation of MUC2 gene expression.…”
Section: Discussionmentioning
confidence: 99%